Concise Synthesis of Lamellarin Alkaloids by C–H/N–H Activation: Evaluation of Metal Catalysts in Oxidative Alkyne Annulation - Mei, Ruhuai; Zhang, Shou-Kun; Ackermann, Lutz (Synlett, 2017)
The performance of various transition-metal catalysts was explored in the step-economical synthesis of naturally occurring lamellarin alkaloids by C–H/N–H activation. The oxidative alkyne annulation proceeded efficiently by using sustainable ruthenium(II) catalysis, which set the stage for a concise synthesis of lamellarin D, lamellarin H and derivatives thereof.
Keywords: alkaloids; C–H activation; lamellarin; natural products; ruthenium